FUNCTION WORDS IN KARAKALPAK LANGUAGE - Jawgasharova Amina Alawaddinovna (KONFERENSIYALAR, 2025)
Abstract. This article presents information about function words in Karakalpak language. It gives exact definitions of function words, their grammatical features and the types of these words in Karakalpak and other languages. Moreover, it defines the connection and relationship of function words with other words in a sentence.